From Notebooks to Institutions: The Case for Symbiotic Cognition - Slors, Marc (Frontiers in Psychology, 2020)
Cognition is claimed to be extended by a wide array of items, ranging from notebooks to social institutions. Although the connection between individuals and these items is usually referred to as ‘coupling’, the difference between notebooks and social institutions is so vast that the meaning of ‘coupling’ is bound to be different in each of these cases. In this paper I argue that the radical difference between ‘artefact-extended cognition’ and ‘socially extended cognition’ is not sufficiently highlighted in the literature. I argue that there are two different senses of ‘cognitive extension’ at play, that I shall label, respectively, ‘implementation extension’ and ‘impact extension.’ Whereas implementation extension is a causal-functional notion, impact-extension hinges on social normativity that is connected with organization and action coordination. I will argue that the two kinds of cognitive extension are different enough to warrant separate labels. Because social extension of cognition involves the reciprocal co-constitution of cognitive capacities, I will propose to set it apart from other types of extended cognition by using the label ‘symbiotic cognition.